2017
DOI: 10.3390/coatings7080117
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Fluorinated Hydrophobic UV-Crosslinkable Thiol-Ene Polyurethane Coatings

Abstract: Abstract:The polyurethane prepolymer terminated with a double bond was synthesized using isophorone diisocyanate (IPDI), hydroxyl terminated polybutadiene (HTPB), 1,4-butanediol (BDO), and 2-hydroxyethyl acrylate (HEA). Then, a series of innovative UV-curable polyurethane coatings were prepared by blending ene-terminated polyurethane, fluoroacrylate monomer, and multifunctional thiol crosslinker upon UV exposure. The incorporation of fluoroacrylate monomer and multifunctional thiols into polyurethane coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The results of NOPs modification experiments on PUDs provide an effective basis for the selection of adhesives for high-performance polyurethane coatings in the future, and effectively promote the steady progress of green production of polyurethane coatings. Xia and Zhu (2017) used fluoroacrylate monomers and multifunctional mercaptans to blend and modify polyurethane, and their study found that the durability, yellowing resistance and elongation at break of the modified polyurethane coating were significantly improved. However, the current research on polyurethane modification technology cannot fully meet people’s performance requirements for polyurethane coating materials.…”
Section: Coated Polymer For Cut-resistantmentioning
confidence: 99%
“…The results of NOPs modification experiments on PUDs provide an effective basis for the selection of adhesives for high-performance polyurethane coatings in the future, and effectively promote the steady progress of green production of polyurethane coatings. Xia and Zhu (2017) used fluoroacrylate monomers and multifunctional mercaptans to blend and modify polyurethane, and their study found that the durability, yellowing resistance and elongation at break of the modified polyurethane coating were significantly improved. However, the current research on polyurethane modification technology cannot fully meet people’s performance requirements for polyurethane coating materials.…”
Section: Coated Polymer For Cut-resistantmentioning
confidence: 99%
“…Thermoplastic polyurethane (TPU) elastomer, a segmented block copolymer, composed of alternant soft segments (SSs) and hard segments (HSs) exhibits microphase separation and supramolecular networks depending on the intersegmental interactions between SSs and HSs. TPUs have been used in many fields, such as heat storage, dielectric materials, shape memory, , drug delivery, cardiovascular prosthetics, wear-resistant endoprosthesis, sorbent materials, and UV-curable coating . The SSs provide flexibility and elasticity with low glass transition temperature ( T g ) below ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that polyurethanes have increasingly attracted attention because of their outstanding properties and wide applications in foams, plastics, rubber, and coatings [1][2][3]. As a member of the polyurethane family, polythiourethanes (PSU) are formed by a reaction of isocyanates or isothiocyanate with polyols, polythiols, water, and amines containing an active hydrogen atom [4,5].…”
Section: Introductionmentioning
confidence: 99%